1997
DOI: 10.1063/1.118658
|View full text |Cite
|
Sign up to set email alerts
|

Violet/blue emission from epitaxial cerium oxide films on silicon substrates

Abstract: Violet/blue photoluminescence was observed from epitaxial cerium oxide films on silicon substrates. The films were deposited on silicon (111) substrates under ultrahigh vacuum conditions using pulsed laser ablation of a cerium oxide target and treated by rapid thermal annealing in argon. High resolution transmission electron microscopy and x-ray diffraction measurements indicated the formation of a single crystal cerium oxide phase Ce6O11 different from CeO2 in the annealed films. The emission might be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(104 citation statements)
references
References 11 publications
3
97
1
3
Order By: Relevance
“…The emission spectra of calcined CeO 2 NPs excited under 386 nm wavelength as shown in Fig. 15b, e. The spectra exhibits characteristic peaks at * 485, 528 and 542 nm are believed to be due to surface defects and oxygen vacancies (Li et al 2011;Arunkumar et al 2014;Morshed et al 1997;Maensiri et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The emission spectra of calcined CeO 2 NPs excited under 386 nm wavelength as shown in Fig. 15b, e. The spectra exhibits characteristic peaks at * 485, 528 and 542 nm are believed to be due to surface defects and oxygen vacancies (Li et al 2011;Arunkumar et al 2014;Morshed et al 1997;Maensiri et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The violet emission band centered at 412 nm for CeO 2 NPs is attributed to defect states existing extensively between the Ce 4f state and O 2p valence band 25 . The two blue emissions are observed at 444 nm and 460 nm for CeO 2 NPs and this is due to localization of the energy levels between the Ce 4f band and the O 2p band.…”
Section: Ftir Analysismentioning
confidence: 99%
“…[38À41] Morshed et al [41] observed a wide PL emission band from 325 to 550 nm in CeO 2 nanoparticles. The emission peaks have been attributed to (1) oxygen deficient ceria Ce 6 O 11 , (2) charge transitions from the 4f band to the valence band of the CeO 2 , (3) surface defects, (4) defects in energy levels between Ce 4C (4f) and O 2¡ (2p) level resulting in hopping of electrons.…”
Section: Photoluminescence (Pl) Studiesmentioning
confidence: 99%